OPTIMIZING PRIMARY SCHOOL STUDENTS' PARENTAL INVOLVEMENT IN ONLINE LEARNING - Iffah Budiningsih; Tryanti Abdulrahman (Akademika : Jurnal Teknologi Pendidikan, 2022)
The new method of online learning at home has raised some serious concerns for parents. The present study aims to identify the obstacles students might face in online learning; based on the obstacles, the study intends to formulate several recommendations for improvement regarding online learning in primary school. The research method is a survey with 109 parents of elementary school students as the respondents. The data were collected by closed and open questionnaires and were further analyzed in a descriptive by applying a percentage. The results showed that: a) parents are often overwhelmed in assisting their children during the online learning process; b) as professional educators, teachers still bear an important role within the learning process that is irreplaceable by the parents (who have lesser pedagogic competence compared to the teacher); c) the involvement of parents, particularly mothers, is essential within online learning assistance to ensure a comfortable and enjoyable learning experience; d) intensive communication and coordination between parents and teachers/school authoritative is necessary for online learning preparation; e) teachers are encouraged to optimize their pedagogic competence to employ creative methods and interactive learning media; f) in the practical situation, teachers focus on developing motoric aspects and emotional development (particularly arts and religion).